Quality Improvement Plan for Leather Sandal Products to Reduce Defects - Yusuf Mauluddin; Dewi Rahmawati; Azmi Akmal Lutfi; Ripki Abdul Aziz (International Journal of Business, Economics, and Social Development, 2023)
CV. Rama Raiders was a home industry engaged in the fashion sector. The business had seven main stages of the production process: selecting materials, making patterns, cutting techniques, sewing processes, gluing processes, finishing/quality control, and packaging in carrying out production activities to achieve the desired quality CV. Rama Raiders still faces several obstacles, one of which is the presence of defective products produced, which causes product quality to decline. This research aims to identify the factors that cause sandals defects in CV. Rama Raiders. The methodology used the Seven tools and FMEA methods to determine the process of controlling leather sandal product defects using qualitative data. Corrective action plans used the 5W+1H concept to address each root cause of the problems. The results were that the most dominant type of defect in leather sandals was a type of glue defect that was not neat. The appearance was because of human and machine factors that didn't work optimally, tools that didn't support it, materials that didn't fit, inadequate environment, and no standard operating procedures. The improvements made by changing the glue, adding a brush, and making SOP improved the quality. From this research, the methods help reduce the problem of product defects experienced by the company